Acomparative Anatomical Study of the Species Aster subulatus and Aster tripolium (Asteraceae) inTikrit- Iraq. - Hisham majeed shlash (Tikrit Journal of Pure Science)
The two species Aster subulatus and Aster tripolium have been studied in the present study. It involves an anatomical study of epidermis of the leaf, the anatomical characters of diameters, and the numbers of epidermal cell stomata and Indumentum are found to be considerable in taxonomic value which separated and diagnostic both species. The abesence of the hairs on both sides upper and lower epidermis of the leaf have been showed. Also there are many differences in average of stomata numbers on both epidermis surfaces in both studied species. So the characters Also queditatie such as the shape and thickness of epidermis and the stomata are found to be with taxonomic value.